Atalychestvo as a worldview aspect of children's protection in social experience of the Dagestan highlanders: guidelines, categories, values - Gadzhi Magomedkamilovich Guseynov; Razhabat Magomedkamievna Gichibekova; Larisa Kurbanovna Shabanova (Вестник Майкопского государственного технологического университета)
The article considers the problem of the origin and development of the “atalychestvo” institution, as one of the customs that existed in the past among the Dagestan peoples, which has practically disappeared in the modern period. In our opinion, the investigated problem will help to reveal the features of the social education of children and provide them with social protection in difficult life situations. The characteristics of this custom given in the article give us an idea of the causes and specifics of the atalychestvo functioning. The research is relevant due to the fact that public institutions, including atalychestvo, has important theoretical and practical significance in the context of global processes, in which the historical past and the specifics of the development of various peoples, with pronounced ethnic features, are ignored. It should also be noted that the origin, history, true nature and social significance of this phenomenon have not fully explained yet. Currently, atalychestvo is considered to be a surviving and endangered phenomena, and thereby attracts quite justified attention of the scientific community. There is an evidence of the existence of atalychestvo in the past for many Caucasian peoples, and the term “atalychestvo”, established in the Caucasian literature, was taken from the word “atalyk”, which was the name of the person who took the child to be raised. Particular attention is paid to the study of this phenomenon in the context of the historical evolution of the Dagestan peoples, which have both general and special features of development. In the study of various aspects of the investigated problem the authors have used rich source material on the subject, in particular, the works and memoirs of contemporaries of the described events and phenomena.